Exploring the Digital Literacies of Refugees from a Funds-of-knowledge Perspective - Molin-Karakoc, Linda Marie Isabelle (Journal of Ethnic and Cultural Studies, 2025)
Despite multiple assets in the form of languages, cultures and community-based knowledge, refugee students frequently confront barriers in education, including having their rich repertoires of cultural and linguistic knowledge dismissed by teachers (Hos, 2019; Shapiro et al., 2018). Rapidly advancing digital technologies have shifted understandings of language and literacy beyond traditional conceptions, raising the question of how students’ digital practices could be integrated to overcome deficit orientations. Informed by the notions of ‘digital literacies’ (Jones & Hafner, 2021) and ‘funds of knowledge’ (Moll et al., 1992), the present study seeks to explore research on refugees’ digital literacies, including their potential for facilitating asset-based practices in language and literacy education. A scoping literature review was conducted to summarize and synthesize existing knowledge on the topic. A search was performed using a set of keywords and three databases (ERIC, ProQuest, and Google Scholar), resulting in the identification and analysis of 31 papers. The findings indicate that research on refugees’ digital literacies encompasses various geographical contexts, refugee groups, ages, methodologies, and tools, with some areas receiving more extensive research than others. The findings additionally reveal five themes of incorporating refugee learners’ digital literacies to facilitate asset-based pedagogy, including bridging informal and formal practices, utilizing multimodal technology for identity affirmation, promoting agency through choice of language or mode, establishing social relationships, and fostering intercultural online communities. The study concludes with recommendations for practitioners and researchers to enhance further the reciprocity between refugees’ digital literacies and the literacy practices promoted by educators and educational institutions.